A pilot study on the implementation of a model for evaluating school guidance programs - Corpus, Maria Cristina (Animo Repository, 1977)
This research paper sought to determine the workability of an adapted evaluation model in selected schools on the secondary level. Three secondary schools were chosen as pilot test sites, namely, a girl's high school, a public high school, and a missionary high school. The three data-collection instruments integrated in the pilot model were subjected to a trial run. The student needs assessment survey was administered to a randomly selected group of forty, fourth year high school students, enrolled in a middle-sized secondary school. Then, time analysis of counselor functions was given to seven counselors from three high schools and two colleges. The instrument was then revised through the inclusion of a scale, which enabled counselors to estimate actual time distributions over a list of guidance functions, ranging from high priority to low priority functions. Then, the same group of counselors, to see if it would require further changes, did an inspection of the guidance program log. When all the details concerning the pilot study had been threshed out, the counselors set the dates for the implementation phrase in their respective schools. When all the details concerning the pilot study had been threshed out, the counselors set the dates for the implementation phrase in their respective schools. More specifically, it attempts to answer the two major questions posed in this study, namely: 1) How was the preliminary implementation of the pilot model carried out in the pilot schools? 2) How did the student sample react on the Student Needs Assessment Survey?